SUPERVISI KEPALA SEKOLAH TERHADAP GURU MATA PELAJARAN UJIAN NASIONAL DI SMPN 2 RAMBATAN - Zulhadi Zulhadi (al-fikrah: Jurnal Manajemen Pendidikan, 2019)
The problem of this research is "Supervision of Principal to the National Examination Subject Teachers in SMP N 2 Rambatan". And the purpose of this recearch is to describe How Supervision of Principal to the National Examination Subject Teachers in SMP N 2 Rambatan. This research is a qualitative case study method. The main instrument of this research is the researcher himself, and the supporting instruments are a tape recorder, interview guides and other documents. To obtain the required data, the researcher used techniques include observation, documentation and the principal interviews national examination subject teachers.The results of the research based on observation, interviews and documentation, the researcher can take some conclusions as follows: (1) Planning of supervision programs of principal to develop the competence of the National Examination Subject Teacher in order to get the maximum result, (2) Implementation of supervision programs of principal to develop the competence of the National Examination Subject Teacher in order to get the maximum result, (3) Evaluation and follow-up supervision programs of principal to develop the competence of the National Examination Subject Teacher in order to get the maximum result. Based on how the overall Supervision of Principal to the national examination subject teachers is not maximized. This is evident from the evaluation and follow-up of the supervision itself did not cover all aspects of supervision.